2021
DOI: 10.1186/s12920-021-00972-5
|View full text |Cite
|
Sign up to set email alerts
|

A five metastasis-related long noncoding RNA risk signature for osteosarcoma survival prediction

Abstract: Background Osteosarcoma is a highly malignant and common bone tumour with an aggressive disease course and a poor prognosis. Previous studies have demonstrated the relationship between long noncoding RNAs (lncRNAs) and tumorigenesis, metastasis, and progression. Methods We utilized a large cohort from the Therapeutically Applicable Research to Generate Effective Treatments (TARGET) database osteosarcoma project to identify potential lncRNAs related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
1
5
1
Order By: Relevance
“…Based on the risk scores, we divided the patients into a high-risk group (>0.975) and a low-risk group (<0.975), and then calculated the five-year survival rate by Kaplan–Meier analysis. In comparison with other signatures, our AUC value of 0.784 was larger than the 0.745 AUC value of SiYuan Yu’s signature ( Yu et al, 2021 ). This confirmed that our prognostic signature was convincing and had the potential to evaluate the survival of patients with osteosarcoma.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Based on the risk scores, we divided the patients into a high-risk group (>0.975) and a low-risk group (<0.975), and then calculated the five-year survival rate by Kaplan–Meier analysis. In comparison with other signatures, our AUC value of 0.784 was larger than the 0.745 AUC value of SiYuan Yu’s signature ( Yu et al, 2021 ). This confirmed that our prognostic signature was convincing and had the potential to evaluate the survival of patients with osteosarcoma.…”
Section: Discussioncontrasting
confidence: 73%
“…Although several previous studies have identified a series of lncRNAs that play an important role in osteosarcoma, proof of the efficacy of lncRNAs as prognostic markers of osteosarcoma is still limited. SiYuan Yu et al identified a five-lncRNA, metastasis-related risk signature for osteosarcoma survival prediction, and the AUC for predicting 5-year survival was 0.745 ( Yu et al, 2021 ). Gao et al (2020 ) constructed a multivariable Cox regression model based on seven lncRNAs for prognosis prediction, among which AC011442.1 was assumed to act as an oncogenic driver in osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…The four EMGs identified included the well-characterized genes MYC, TERT, EIF4E3, and RBM34 [ 73 ]. Consulting the same TARGET database, Yu et al, 2021 found that five lncRNAs (RP11-128N14.5, RP11-231/13.2, RP5-894D12.4, LAMA5-AS1, and RP11-346L1.2) served as a reliable prognostic signature for OS patients with an AUC (area under the curve) prediction for the 5-year survival rate at a 0.745 accuracy [ 74 ]. Both of these studies offer promise for improving the prognoses of OS patients.…”
Section: Treatmentsmentioning
confidence: 99%
“…Similarly, high level of HULC is also link to poor prognosis of OS patients (83, 84). Yu and colleagues interrogated the OS dataset from TARGET (84). Among a total of 97 samples that have RNA-seq results, they found 24 metastatic samples and 73 non-metastatic samples; and then identified RP11-128N14.5, RP11-231|13.2, RP5-894D12.4, LAMA5-AS1 and RP11-346L1.2 as metastasis-related lncRNAs that can be used as potential prognostic indicator for OS.…”
Section: Lncrna Acts As a Predictive Biomarkermentioning
confidence: 99%